Iron Powder Promoted Regio-Selective Friedel-Crafts Acylation of Indole Under Solvent-Free Conditions - Zhang, Lirong; Yi, Fengping; Zou, Jianzhong; Qu, Shaoyan (Asian Journal of Chemistry, 2013)
A facile, efficient and environment-friendly protocol for the regioselective synthesis of 3-acyl indoles has been developed by one-pot catalytic Friedel-Crafts acylation of indole in presence of the iron powder as catalyst under solvent-free conditions at room temperature.